Everything that Rises Must Converge: How the Policy and Public Responses to Covid-19 in the Education Sphere Impact on Virus Transmission - Eleftheriou, Konstantinos; Ioakimidis, Marilou; Johnes, Geraint (Review of Economic Analysis, 2024)
This paper studies the variation across countries in mortality rates due to COVID-19. A two-stage approach is used to model international data on the spread of COVID-19. The first stage applies a convergence club framework to identify clusters of countries within which the development of the epidemic is similar. The second stage models the membership of these clusters as a function of policy responses and public responses to the pandemic, with a particular focus on education as a determinant of the public response. Data include COVID-19 mortality per million, tertiary education completed, age structure, and voice and accountability and government effectiveness measures for each country in the dataset. We find evidence of two convergence clubs, one with a higher and one with a lower COVID-19 death rate. We also find evidence to support the hypothesis that relatively high levels of educational attainment in a population predicts a lower COVID19 death rate among individuals 65 or more years of age. We speculate that this is attributable to more informed prosocial behaviors directed toward elderly people in the form of adherence to guidelines intended to reduce spread of the virus.